2002
DOI: 10.1073/pnas.011569399
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of macrophage migration inhibitory factor (MIF) tautomerase and biological activities by acetaminophen metabolites

Abstract: The cytokine macrophage migration inhibitory factor (MIF) has emerged to be an important regulator of the inflammatory response and is critically involved in the development of septic shock, arthritis, and glomerulonephritis. Although the biological activities of MIF are presumed to require a receptor-based mechanism of action, the protein is also a tautomerase and has a catalytically active N-terminal proline that is invariant in structurally homologous bacterial isomerases. This observation raises the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
150
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 148 publications
(156 citation statements)
references
References 51 publications
4
150
0
Order By: Relevance
“…Unfortunately, L-Trp Schiff base compounds lack long term stability. We also have shown that a P450-dependent metabolite of acetaminophen, N-acetyl-p-benzoquinone imine (NAPQI), covalently binds to MIF at its enzymatic site (23). The NAPQI adduct inactivates MIF cytokine activity in a number of in vitro bioassays, including interference with the anti-inflammatory effect of dexamethasone, After incubation with FL-ISO1, the cells were washed with PBS and fixed using 4% formaldehyde.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, L-Trp Schiff base compounds lack long term stability. We also have shown that a P450-dependent metabolite of acetaminophen, N-acetyl-p-benzoquinone imine (NAPQI), covalently binds to MIF at its enzymatic site (23). The NAPQI adduct inactivates MIF cytokine activity in a number of in vitro bioassays, including interference with the anti-inflammatory effect of dexamethasone, After incubation with FL-ISO1, the cells were washed with PBS and fixed using 4% formaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…The medium was then replaced with ISO-1-free medium. The cells were then lysed and the tautomerase activity determined (17,23) (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…The involvement of the MIF catalytic site in biological activity has also been studied using small molecule inhibitors (37,38). We have previously studied a series of pharmacological inhibitors of MIF that were designed utilizing the known information about the MIF-binding site and the known chemical structures of substrates of MIF.…”
Section: Iso-1 Inhibits Dopachrome Tautomerase Activity Of Mif-mentioning
confidence: 99%
“…We have generated a series of pharmacological inhibitors of MIF based on structure-activity studies of other inhibitors and a non-physiological substrate. An acetaminophen metabolite, N-acetylbenzoquinone imine, forms a covalent bond with MIF and inhibits MIF catalytic activity (37). We recently used rational design and synthesis of p-hydroxyphenyl Schiff bases as inhibitors of MIF enzymatic activity (38).…”
mentioning
confidence: 99%
“…9 While the physiological role of the tautomerase activity is uncertain, we have previously found that compounds, which are structurally similar to D-and L-dopachrome, could bind to, and thereby block the MIF's tautomerase active site. 4,[10][11][12][13] We have previously shown that N-acetyl-p-benzoquinone imine (NAPQI) forms a covalent complex with MIF at its active site (Scheme 1) and is capable of irreversibly inhibiting the adverse biological effect of MIF. 13 However, the toxicity of NAPQI precluded its use as a viable clinical inhibitor of MIF and the development of non-toxic small molecule inhibitors of MIF tautomerase activity warranted further investigation.…”
mentioning
confidence: 99%